Hubungan Bauran Pemasaran dengan Kepuasan Pasien Rawat Jalan RSI Ibnu Sina Bukittinggi - Yollanda Aulia Fidi; Elsa Luvia Harmen; Meri Herliza (Pusat riset dan Inovasi Nasional, 2025)
Hospitals as a health service industry are required to provide quality services through marketing strategies so that the quality of health services in hospitals becomes higher. One strategy that can be used by hospitals is to implement the Marketing Mix. From the results of initial interviews, it was found that most patients were elderly patients at RSI Ibnu Sina Bukittinggi who had difficulty getting information through social media, resulting in a backlog of registrations and decreased patient satisfaction. This study aims to determine the relationship between the marketing mix and outpatient satisfaction at RSI Ibnu Sina Bukittinggi. This study uses a quantitative method with a cross-sectional design. The sample used was 100 respondents taken from the outpatient population. Data analysis was carried out using the Chi-Square statistical test at α = 0.05 to see the significance of the relationship between the marketing mix and patient satisfaction. The results of the study found that there was a relationship between the product marketing mix and patient satisfaction and there was no relationship between the marketing mix of price, promotion, people, process, physical evidence and outpatient satisfaction. Based on the results of the study, it is expected that the marketing mix in the Outpatient Unit of RSI Ibnu Sina Bukittinggi will maintain and improve its marketing services.